Assessment on cold chain management system in selected blocks of Purulia district, West Bengal, India - Haldar, Mandira; Majumdar, Kunal Kanti; Ghosh, Pramit (International Journal Of Community Medicine And Public Health, 2022)
Background: The study was done to assess the status of cold chain point, vaccine storage practice and practice of health workers about immunization activities at cold chain points. The aim was to evaluate the cold chain system in relation to infrastructure, manpower and maintenance of equipment in selected blocks of Purulia district. Methods:It was a cross sectional descriptive study, done at randomly selected sites where vaccines were stored and outreach sessions where immunization services were provided. Five cold chain points were included in the study. Fully structured standardized checklists and questionnaire had been used to collect the data. Results: Only 40% cold chain point (CCP) reported breakdown of cold chain equipment (CCE) in last one year. Ice lined refrigerator (ILR) and deep freezer (DF) were properly placed in 75% of the CCP. All the CCP have displayed contingency plans and latest standard job aids. Vaccines and ice packs were correctly placed. ILR and DF were connected to functional voltage stabilizer. A functional thermometer was placed inside every ILR and DF and twice daily recording of temperature was found in all the CCPs. Record of vaccine wastage was found only in 40% CCPs. CCPs have adequate space for conditioning. No frozen vaccine and vaccine vial beyond expiry date were found in any of the CCPs. All CC handlers had satisfactory knowledge about cold chain management. Conclusions:This study was an effort to assess the status of cold chain points in Purulia district, West Bengal. Overall result was satisfactory, could have been maintained and further improve in future by good supportive supervision practice as a key measure in improvement of cold chain system.